2020
DOI: 10.1057/s41267-019-00296-8
|View full text |Cite
|
Sign up to set email alerts
|

Do venture capital firms benefit from international syndicates?

Abstract: This paper examines the benefits of syndicating with foreign venture capital (VC) firms for domestic VC firms in emerging markets. We find that the VC firms that are domestic to their invested companies and previously syndicated with foreign partners invest proportionately more frequently in riskier ventures. After gaining syndication experience with foreign VC firms, a larger number of their portfolio companies successfully exited, thereby suggesting improved performance. We hypothesize that this outcome is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…This shows the role of risk cover played by syndicates and social networks. Exploring the indirect effect of syndication, Khurshed et al (2020) also found that Asian VCs learned from their syndication with North American VCs to invest in early stage ventures and high-tech industries, suggesting non-financial benefits from syndication.…”
Section: Syndicatementioning
confidence: 93%
“…This shows the role of risk cover played by syndicates and social networks. Exploring the indirect effect of syndication, Khurshed et al (2020) also found that Asian VCs learned from their syndication with North American VCs to invest in early stage ventures and high-tech industries, suggesting non-financial benefits from syndication.…”
Section: Syndicatementioning
confidence: 93%
“…They learn from their foreign VC partners, and knowledge and skills give them confidence and improve their subsequent investment decisions. (Khurshed et al, 2020) The pressure of political culture on the emerging relations between participants of EE in the long term is weakening, thanks to a change in political culture towards the complementarity of public and private investments and less regulatory interference. The state, initiating the creation of EE, seeks to establish EE on its territory.…”
Section: Discussionmentioning
confidence: 99%
“…Different VC firms may have different strengths in terms of connections, capital, and social networks (Brander et al, 2002), so that they can guide companies in their innovation activities more comprehensively and provide resources in various areas of expertise to their portfolio companies, thus avoiding abortive innovation activities due to lack of industry experience and expertise. In addition, VC firms can also learn from other partners through cross-border syndication to make up for their internal knowledge deficiencies and improve investment performance (Khurshed et al, 2020). Therefore, from the perspectives of risk sharing and value addition, it can be found that VC cross-border syndication is beneficial to reducing risk and integrating entrepreneurial resources to help startups grow.…”
Section: Venture Capital Cross-border Syndicationmentioning
confidence: 99%
“…Another important factor that may interfere with the reliability of the baseline regression results is the sample selection bias. Khurshed et al (2020) found that syndication with foreign VCs will change the investment behavior of domestic VC firms, and the richer the syndication experience with foreign VC firms, the more likely domestic VC firms are to invest in high-tech or early-stage startups. Therefore, based on the findings of Khurshed et al (2020), the baseline regression results in this paper may have a sample selection bias, that is, the experience of cross-border syndication of domestic VCs may have changed their criteria and ability to select projects that can help them choose more innovative companies as investment targets.…”
Section: Test Of Sample Selection Biasmentioning
confidence: 99%